2009
DOI: 10.1080/01587910903236551
|View full text |Cite
|
Sign up to set email alerts
|

Student and tutor perceptions of effective tutoring in distance education

Abstract: Questionnaire responses of 457 students and 602 tutors were used to investigate conceptions of a 'good tutor'. In each case, factor analysis identified scales that reflected key constructs; cluster analysis identified subgroups with different patterns of scale scores; and discriminant analysis determined the scales that contributed the most to differences among the clusters.Both sets of data yielded conceptions of tutoring that were described as task-oriented and student-oriented, respectively. The students' d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 26 publications
2
36
0
1
Order By: Relevance
“…Subject matter expertise should therefore also cover proficiency in the target language, which is perceived to be a characteristic of effective language teachers (Brosh, 1996). As in the conventional language setting, Jelfs et al (2009) found that both tutors and distance students value tutors' subject matter expertise. In another study which examined both tutor and student views on distance language learning, both groups agreed that tutors should "have native or near-native speaker competency" (Murphy et al, 2010, p. 125).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subject matter expertise should therefore also cover proficiency in the target language, which is perceived to be a characteristic of effective language teachers (Brosh, 1996). As in the conventional language setting, Jelfs et al (2009) found that both tutors and distance students value tutors' subject matter expertise. In another study which examined both tutor and student views on distance language learning, both groups agreed that tutors should "have native or near-native speaker competency" (Murphy et al, 2010, p. 125).…”
Section: Introductionmentioning
confidence: 98%
“…The teacher's personal relationship with the students may therefore influence the latter's learning motivation (Ghanizadeh & Moafian, 2010;Oxford, 1998). A good tutor-student relationship is particularly important in distance education given the frequent separation of tutors and students in space and/or time (Jelfs, Richardson, & Price, 2009;Murphy et al, 2010;Shelley et al, 2006). According to the tutor Maxim of Honesty, that is, "work for an honest, supportive relationship," identified by White et al (2005) in their work with distance language tutors, teachers should be able to "provide accurate feedback, encouragement, and support in such a way that the student feels 'reassured, valued and respected'" (p. 93).…”
Section: Introductionmentioning
confidence: 99%
“…Four components of tutor's perceptions of tutoring have been investigated in the literature: their perceptions of their role as tutors and the purpose of tutoring (Colvin, 2007;Moore, 2009;Bailey, 2010;Galbraith and Winterbottom, 2011), characteristics of effective tutors (Jelfs et al, 2009;Xiao, 2012), characteristics of tutees (Bailey, 2010), and characteristics of effective tutoring (Wood et al, 1976;Topping, 1996;Lepper et al, 1997;Falchikov, 2001).…”
Section: Tutors' Perceptions Of Tutoringmentioning
confidence: 99%
“…Cole, 2009;Feldman, 2007;Jelfs, Richardson, & Price, 2009;Lawrence & Sankey, 2008;Lee, 2008;Oliver, Osborne, & Brady, 2009) have found that the unique characteristics of a virtual community are likely to create in students a sense of personal empowerment that enhances the learning process. The learning environment must enable a dynamic process in which students feel safe to be active participants (Pelz, 2004;Splitter, 2009).…”
Section: Social Presencementioning
confidence: 99%